Associations of PM2.5 and its components with term preterm rupture of membranes: a retrospective study - Jiangxia Qin; Weiling Liu; Haidong Zou; Chong Zeng; Cifeng Gao; Weiqi Liu (PeerJ)
Background There is evidence that fine particulate matter (PM2.5) exposure is associated with premature rupture of membranes (PROM); however, studies of its effect on term PROM (TPROM) are limited, and the results are inconsistent. Objective This study aimed to investigate the association between exposure to PM2.5 and its components and the risk of TPROM. Methods From 2018 to 2022, we collected delivery data from pregnant women in Guangzhou. Using 1:1 case matching, we included 1,216 TPROM cases and 1,216 controls. PM2.5 and its component concentrations were obtained from Tracking Air Pollution in China. The time-varying mean concentration method was used to estimate exposure to PM2.5 and its components during different trimesters. Cox proportional hazards models were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) to evaluate the associations of exposure to PM2.5 and its components with the risk of TPROM. Results The incidence of TPROM in this study was 19.66%. After adjusting for potential confounders, statistically significant associations were found between TPROM and exposure to PM2.5, nitrate ( ${NO}_{3}^{-}$ NO 3 − ), ammonium ( ${NH}_{4}^{+}$ NH 4 + ), and black carbon (BC) during the second trimester and between TPROM and exposure to PM2.5, sulphate ( ${SO}_{4}^{2-}$ SO 4 2 − ), and BC during the third trimester. Specifically, the interquartile range (IQR) 3 (IQR3) and IQR4 of ${SO}_{4}^{2-}$ SO 4 2 − exposure during the third trimester increased the risk of TPROM by 18% (95% CIs [1.01–1.39]) and 18% (95% CIs [1.01–1.39]), respectively. A nonlinear relationship was observed between exposure to PM2.5, ${SO}_{4}^{2-}$ SO 4 2 − , ${NH}_{4}^{+}$ NH 4 + , and OM during the second trimester and the risk of TPROM. No significant interactions were found between PM2.5 and its components with TPROM across various subgroups. Conclusion Our findings indicate significant associations between the risk of TPROM and exposure to PM2.5 and several of its components during pregnancy. Contribute to the literature on the associations of PM2.5 and its components with TPROM.